Regression Equation Model of Motivation, Self-Confidence, and Anxiety Variables in Mastering Badminton Games Learning Outcome Test - Yady Supriyatna; Nurlan Kusmaedi; Yusuf Hidayat; Burhan Hambali (Universitas Pendidikan Indonesia, 2019)
The study was aimed at testing the models of variable regression equations of motivation, self-confidence, and anxiety in the mastery of badminton learning outcomes. The method used in this research was the correlational descriptive method involving 100 badminton school students aged 11-15 years as participants. The research was conducted in the Badminton schools in Bandung City. The instruments used in this study were motivational scales, confidence scales, anxiety scales, and Badminton learning test outcomes. The data obtained were analyzed by using regression method with double regression analysis employing SPSS statistic analysis software for Windows version 21. The results showed that motivation, confidence, and anxiety had a significant impact on the basic learning outcomes of badminton.